STABILITY AND FAILURE OF THIN-WALLED COMPOSITE STRUCTURES WITH A SQUARE CROSS-SECTION - CZAJKA, Błażej; RÓŻYŁO, Patryk; DĘBSKI, Hubert (Applied Computer Science, 2022)
This paper is devoted to the analysis of the stability and load-carrying capacity of thin-walled composite profiles in compression. The specimens reflect elements made of carbon fibre reinforced laminate (CFRP). Thin-walled columns with a square crosssection were made from 4 layers of composite in 3 different combinations of layer arrangements. Advanced numerical analyses have been carried out. In the first stage of the study, a buckling analysis of the structure was performed. In further numerical simulations, two advanced models were used simultaneously: the Progressive Failure Analysis (PFA) and the Cohesive Zone Model (CZM). The results showed significant differences between the critical load values for each layer configuration. The forms of buckling and the areas of damage initiation and evolution were also dependent on the applied layup.